2010
DOI: 10.4104/pcrj.2010.00002
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up survey of general practitioners' perceptions of UK allergy services

Abstract: Background: A UK survey of general practitioners (GPs) in 2002 found that they perceived allergy care throughout the UK National Health Service (NHS) to be poor. We conducted a follow-up survey in 2009 to see if GPs' perceptions had changed.Objectives: To determine GP perceptions of allergy care in the NHS in the wake of recent Government reports into allergy care, and to compare the findings of this survey to a similar survey conducted in 2002.Methods: A cross-sectional postal survey of 500 UK GPs was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 5 publications
0
21
2
Order By: Relevance
“…In comparison with a UK survey of GPs performed in 2009 which found that only 29% of GPs surveyed had received allergy training, 10 the results of this study suggest that the current cohort of trainees may be receiving more training in allergy. More generally, the concerns about the perceived management of systemic allergic reaction -particularly food allergy -echo the findings of the earlier GP surveys, 9,10 highlighting the fact that training centred on these disorders is likely to be perceived as useful by both GP trainees and more established GPs.…”
Section: 13contrasting
confidence: 63%
See 3 more Smart Citations
“…In comparison with a UK survey of GPs performed in 2009 which found that only 29% of GPs surveyed had received allergy training, 10 the results of this study suggest that the current cohort of trainees may be receiving more training in allergy. More generally, the concerns about the perceived management of systemic allergic reaction -particularly food allergy -echo the findings of the earlier GP surveys, 9,10 highlighting the fact that training centred on these disorders is likely to be perceived as useful by both GP trainees and more established GPs.…”
Section: 13contrasting
confidence: 63%
“…In comparison with a UK survey of GPs performed in 2009 which found that only 29% of GPs surveyed had received allergy training, 10 the results of this study suggest that the current cohort of trainees may be receiving more training in allergy. More generally, the concerns about the perceived management of systemic allergic reaction -particularly food allergy -echo the findings of the earlier GP surveys, 9,10 highlighting the fact that training centred on these disorders is likely to be perceived as useful by both GP trainees and more established GPs. The recent publications of national guidelines on food allergy and anaphylaxis by the National Institute for Health and Clinical Excellence (NICE) 14,15 and anaphylaxis guidelines by the World Allergy Organization 16,17 should create a further impetus for improved training in these important clinical areas.…”
Section: 13contrasting
confidence: 63%
See 2 more Smart Citations
“…A recent survey of GPs found that only 9% had received allergy training. 77 Allergy testing, essential to accurate diagnosis and treatment, is rarely conducted in primary care: skin prick testing is only rarely available 77 and specific IgE testing although widely available is rarely used. Practices have open access to blood tests and radiology services, oximetry is increasingly available, but in some …”
Section: Facilities In Primary Carementioning
confidence: 99%